A preliminary study on knowledge acquisition and requirement among SME Entrepreneurs / Roslilee Ab Halim, Sharifah Zannierah Syed Marzuki and Noor Affeeda Ramli - Ab Halim, Roslilee; Syed Marzuki, Sharifah Zannierah; Ramli, Noor Affeeda (2013)
In order to engage in business, entrepreneurs should equip themselves with sufficient knowledge on how to run the business. Generally, the knowledge of business management being acquiredincludes finance. marketing, accounting, operation management and business development. The level of knowledge attained has been significantly proven in literature to have a positive impact on business performance. As small and medium enterprise (SME) is seen as one of the important economic engines in Malaysia. it is very important to ensure that SME entrepreneurs are well equipped with the knowledge to be able to perform and survive in the market. Therefore. this preliminary study is conducted in order to investigate the level of knowledge acquisition and knowledgerequirement of SME entrepreneurs. A total of 50 self-administered questionnaireswere distributed to SME entrepreneurs in Bandar Tun Abdul Razak Jengka. The data was tabulated using SPSS version 20.0 for descriptive statistics. The findings are expected to deliver a positive connotation with the academic professionals to deliver theoretical and hands on knowledge for the SME entrepreneurs in enhancing their business knowledge and simultaneously having good business practices.